The effects of basement faults on thermal convection and implications for the formation of unconformity‐related uranium deposits in the Athabasca Basin, Canada. Issue 4 (4th June 2016) - Li, Z.; Chi, G.; Bethune, K. M.
Abstract: The formation of the world‐class, high‐grade unconformity‐related uranium deposits in the Athabasca Basin (Canada) requires circulation of large amounts of fluids, the mechanisms for which are still not well understood. Recent studies advocate thermal convection as a possible driving force for the fluid flow related to uranium mineralization; however, little is known regarding how basement faults, which are spatially associated with most unconformity‐related uranium deposits, influence fluid convection and how this may affect the localization of mineralization. This study addresses these questions through simulations of thermal convection with various configurations of basement faults using the FLAC3D software. Modelling results indicate that the location, spacing, orientation and thermal conductivities of basement faults influence the size and location of thermally driven fluid convection. In a model with a single isolated fault, the fault coincides with an upwelling plume and the dip angle of the fault does not affect the fluid flow pattern; when the fault is moved laterally, the upwelling plume shifts accordingly. In the case of two vertical faults, the faults may either coincide with upwelling flow between two convection cells or be located below individual convection cells, depending on fault spacing. In the latter case, fluid may flow into and out of individual fault zones. Similar results were also obtained for models with two nonvertical (i.e. dipping) faults. Convective flow can penetrate the uppermost basement when the permeability is less than two orders of magnitude lower than that of the overlying sandstone. In this case, the basement faults not only can control the location of ascending flow, but also can passively act as fluid conduits of either flow from the basin into the basement (ingress), or flow from the basement into the basin (egress), depending on their thermal conductivities and relative locations in the models.